A Masked Cuprous Hydride as a Catalyst for Carbonyl Hydrosilylation in Aqueous Solutions. Issue 6 (3rd January 2019) - Ritter, Florian; Mukherjee, Debabrata; Spaniol, Thomas P.; Hoffmann, Alexander; Okuda, Jun
Abstract: Redox‐unstable cuprous hydridotriphenylborate was isolated as an N‐heterocyclic carbene adduct [(IPr)Cu(HBPh3 )] (IPr=1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene) with good thermal stability. Although this compound displays a contact ion‐pair structure, Cu I H‐like catalytic activity was envisaged in carbonyl hydrosilylation. Sufficient moisture stability allowed the catalysis in aqueous/organic media. Mechanistic study further showed that a phenyl group on the borate anion is abstracted by [(IPr)Cu] + to give the cationic organocopper complex [(IPr)2 Cu2 (μ‐Ph)][BPh4 ]. Abstract : Monomeric Cu(HBPh3 ) supported by an N‐heterocyclic carbene is thermally stable and catalyzes the carbonyl hydrosilylation in water as a co‐solvent.